RELEVANSI NILAI-NILAI KEWIRAUSAHAAN DALAM MATERI PAI BP SMA SEDERAJAT K13 REVISI 2020 - Hamdan Adib; Suriyah Suriyah; Siti Fatimah Siregar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The purpose of this research is to find out the relevance of entrepreneurship values in the PAI BP material at SMA Sederajat K13 Revised 2020. This study uses a qualitative method in the type of literature study. The primary source in this research is LKS PAI BP SMA and secondary sources are various literatures that support the research theme. The results of this study indicate that there is a relevance of entrepreneurial values in the PAI BP material in SMA including in class X material, Chapter 3 explains the obligation to study where entrepreneurs must have broad insight, then class XI in Chapter 1 is a work ethic material that has a work orientation. and later results in Chapter 10 related to Islamic economics and various economic practices based on the rules of the Qur'an Hadith and other Islamic legal bases and class XII in Chapter 1 and Chapter 4 which discusses positive thinking, hard work and responsibility is a form of concrete of the leadership values contained in entrepreneurship.